2015
DOI: 10.1186/s12871-015-0112-y
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of arginase inhibitor on lung oxidative stress and inflammation caused by pneumoperitoneum in rats

Abstract: BackgroundPneumoperitoneum-induced oxidative stress and organ injury are known to be associated with nitric oxide (NO) inactivation. Because arginase competes with NO synthase (NOS) for a common substrate, L-arginine, arginase inhibition may increase NO bioavailability. Therefore, we evaluated the ability of the arginase inhibitor, 2 (S)-amino-6-boronohexanoic acid (ABH), to attenuate pneumoperitoneum-induced decrease of NO bioavailability and lung injury.MethodsThirty rats were randomly divided into the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…It is also well known that OS is responsible for the decreased NO bioavailability. 42 Thus, our research evaluated the contribution of NO to endothelialdependent vasodilation, and we found that NO-mediated vasodilation and eNOS protein expression were lower in the SHR-C group than in the WKY-C group. In addition, NO contribution was greater in the SHR-M group than in the SHR-C group, and the the SHR-H group had increased eNOS expression but decreased NO contribution.…”
Section: Discussionmentioning
confidence: 87%
“…It is also well known that OS is responsible for the decreased NO bioavailability. 42 Thus, our research evaluated the contribution of NO to endothelialdependent vasodilation, and we found that NO-mediated vasodilation and eNOS protein expression were lower in the SHR-C group than in the WKY-C group. In addition, NO contribution was greater in the SHR-M group than in the SHR-C group, and the the SHR-H group had increased eNOS expression but decreased NO contribution.…”
Section: Discussionmentioning
confidence: 87%
“…The activity of arginase enzyme was determined as previous described [19]. Briefly, 100 µg/ml BAL fluids were added to the activation solution (50 mmol Tris-HCl and 10 mmol MnCl 2 , pH 7.5).…”
Section: Arginase Activity Assaymentioning
confidence: 99%
“…Rapid infusion and absorption of CO 2 and high pressure pneumoperitoneum increased intraabdominal pressure, leaded to internal and external organs ischemia, increased postoperative pain, and resulted many physiological disorders [10]. Meanwhile, CO 2 harmed organs by promoted oxidative stress and in ammatory response [2]. Studies have shown that the incidence of postoperative delirium and cognitive dysfunction may be related to the in ammatory response of the central nervous system [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…However, in both RALRP and LRP group, patients need to be in CO 2 pneumoperitoneum and placed in Trendelenburg (ST) position to provide effective operating space, which has a great in uence on the physiology of patients during operation and may affect the incidence of postoperative delirium. CO 2 pneumoperitoneum can promote the in ammatory response during surgery [2], which affects the patient's outcomes. At the same time, this effect varies with the change of intra-abdominal pressure(IAP) [3].…”
Section: Introductionmentioning
confidence: 99%